2021
DOI: 10.18502/ijaai.v20i1.5409
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of COVID-19 Entry into the Cell: Potential Therapeutic Approaches based on Virus Entry Inhibition in COVID-19 Patients with Underlying Diseases

Abstract: The Coronavirus disease 2019 (COVID-19) virus spread from Wuhan, China, in 2019 and is spreading rapidly around the world. COVID-19 victims are almost associated with cardiovascular disease, high blood pressure, diabetes, and other underlying diseases. Concerning the high prevalence of these disorders, widespread mortality threatens global society, and its fatality rate may increase with increasing COVID-19 prevalence in countries with older populations. Therefore, evaluating patients' clinical status with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…In vitro and animal models demonstrated that piperine induces toxicity, apoptosis and cell cycle arrest in various tumor cells ( 34 ). Piperine combined with anti-cancer drugs induced more cytotoxicity in human cancer cells ( 20 , 35 , 36 ). Here, we explored the cytotoxic effects of piperine combined with cisplatin and the mechanisms of their effects in breast cancer cells of MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal models demonstrated that piperine induces toxicity, apoptosis and cell cycle arrest in various tumor cells ( 34 ). Piperine combined with anti-cancer drugs induced more cytotoxicity in human cancer cells ( 20 , 35 , 36 ). Here, we explored the cytotoxic effects of piperine combined with cisplatin and the mechanisms of their effects in breast cancer cells of MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…This virus impacts the human body after recovery. The virus penetrates the host cells via angiotensin-converting enzyme-2 (ACE-2) receptors, which are found on different types of peripheral tissue in the human body, such as the kidneys, liver, lungs, and skeletal system, which may lead to disorders in multiple organs [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%